bella_citra25, ##default.groups.name.author##, ANALISIS KESANTUNAN BERBAHASA PADA SISWA KELAS IV SD NEGERI 1 WONOREJO KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG TAHUN AJARAN 2017/2018.docx - Rastranda, Bella Citra; Ratri, Asri Kusumaning (Universitas Nusantara PGRI Kediri, 2019)
Abstract :The purpose of this study is to analyze language politeness in a student's speech that obey and violate the principles of politeness in SD Negeri 1 Wonorejo Academic Year 2017/2018. The methods used in data collection is the observation and interviews are supported by recording techniques and record techniques. The data that have been obtained is then analyzed using the principles of politeness of the rules which have been put forward by Geoffrey Leech. Instruments used in this study are observation sheets and interview guides. The results of this study found the form of polite and disrespectful speech in the fourth grade students of SDN 1 Wonorejo based on Leech's politeness principle. In the observation result the number of maximally single complaint utterances as much as 23 utterances and double maxim as much as 4 speeches. In addition, the number of single maximally infringement sessions of 20 speeches, while double maximizing violations of 6 speeches. In the result of a single maximally single adherence speech interview of 8 speeches, and a single maximal offense of 16 speeches. Single maximization and offense include, maxim of wisdom, maxim acceptance, maxim of generosity, maxim of humility, maxim of suitability, and maxim of conclusions. Double maximizing includes, maximizing wisdom and acceptance, maximization of wisdom and humility, maxim of generosity and humility, and maxim acceptance and suitability. Double maximal offenses include, maxim acceptance and humility, maxim of generosity and humility, and maxim of wisdom and generosity. Keywords : Language Politeness, Principles of Politeness, Speech.